2-Thiopyrimidine/chalcone hybrids: design, synthesis, ADMET prediction, and anticancer evaluation as STAT3/STAT5a inhibitors - Phoebe F. Lamie; John N. Philoppes (Taylor & Francis Group, 2020)
A novel 2-thiopyrimidine/chalcone hybrid was designed, synthesised, and evaluated for their cytotoxic activities against three different cell lines, K-562, MCF-7, and HT-29. The most active cytotoxic derivatives were 9d, 9f, 9n, and 9p (IC50=0.77-1.74 µM, against K-562 cell line), 9a and 9r (IC50=1.37-3.56 µM against MCF-7 cell line), and 9a, 9l, and 9n (IC50=2.10 and 2.37 µM against HT-29 cell line). Compounds 9a, 9d, 9f, 9n, and 9r were further evaluated for their cytotoxicity against normal fibroblast cell line WI38. Moreover, STAT3 and STAT5a inhibitory activities were determined for the most active derivatives 9a, 9d, 9f, 9n, and 9r. Dual inhibitory activity was observed in compound 9n (IC50=113.31 and 50.75 µM, against STAT3 and STAT5a, respectively). Prediction of physicochemical properties, drug likeness score, pharmacokinetic and toxic properties was detected.